2003
DOI: 10.1152/ajprenal.00270.2002
|View full text |Cite
|
Sign up to set email alerts
|

Arginase inhibition slows the progression of renal failure in rats with renal ablation

Abstract: nase inhibition slows the progression of renal failure in rats with renal ablation. Am J Physiol Renal Physiol 284: F680-F687, 2003. First published December 10, 2002 10.1152/ajprenal.00270.2002. Exogenous arginine slows the progression of chronic renal failure (CRF) in remnant rats through a nitric oxide (NO)-dependent mechanism. We tested whether the inhibition of arginase could induce similar results through the increased availability of endogenous arginine. Three groups of remnant rats were studied for 8 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
17
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 38 publications
2
17
0
Order By: Relevance
“…55 Vascular arginase activity is increased in experimental hypertension and inhibition of arginase restores endothelial NO synthesis. [56][57][58][59] Arginase I and arginase II are upregulated in the vasculature of Dahl salt-sensitive rats maintained on a high-salt diet; 58 similar findings have been reported for spontaneously hypertensive rats. 59 Particularly relevant is that inhibition of arginase protects the kidney from structural damage in the 5/6 renal mass ablation/infarction model of CKD, 56 indicating that arginase inhibition might be a novel therapeutic approach to slowing progressive renal damage.…”
Section: Utilization Of Arginine By Non-no-producing Pathwayssupporting
confidence: 67%
See 1 more Smart Citation
“…55 Vascular arginase activity is increased in experimental hypertension and inhibition of arginase restores endothelial NO synthesis. [56][57][58][59] Arginase I and arginase II are upregulated in the vasculature of Dahl salt-sensitive rats maintained on a high-salt diet; 58 similar findings have been reported for spontaneously hypertensive rats. 59 Particularly relevant is that inhibition of arginase protects the kidney from structural damage in the 5/6 renal mass ablation/infarction model of CKD, 56 indicating that arginase inhibition might be a novel therapeutic approach to slowing progressive renal damage.…”
Section: Utilization Of Arginine By Non-no-producing Pathwayssupporting
confidence: 67%
“…23 The kidney contains arginase II, and endothelial cells contain both isoforms. 23,55,56 Arginases compete with NOS for L-arginine and can thereby limit NO production; indeed, NO production is attenuated in endothelial cells overexpressing arginase I and arginase II. 55 Vascular arginase activity is increased in experimental hypertension and inhibition of arginase restores endothelial NO synthesis.…”
Section: Utilization Of Arginine By Non-no-producing Pathwaysmentioning
confidence: 99%
“…For general histology, sections were processed for hematoxylin/eosin, periodic acid-Schiff, and Masson-Trichrome staining. A semiquantitative morphometric score index (SI) was used to evaluate the degree of glomerulosclerosis (22,25). Sclerosis was defined as collapse and/or obliteration of glomerular capillary tuft accompanied by hyaline material and/or increase of matrix.…”
Section: Morphologic Analysismentioning
confidence: 99%
“…It also decreased proteinuria in a 5/6 ablation model of CKD. 37 In contrast, Moradi et al 38 found that there was no difference in arginase I and II protein abundance among CKD and control groups in a rat 5/6 nephrectomy model. Here, high urea concentrations in CKD may inhibit arginase activity, may attenuate l-arginine catabolism, and may mitigate the fall in l-arginine levels.…”
mentioning
confidence: 96%